Analisis Isi Buku Ajar Bahasa Indonesia Cerdas Cergas Berbahasa dan Bersastra Indonesia untuk Kelas X SMA - Ginanjar, Agi Ahmad; Kartadireja, Welly Nores; Astriani, Aveny Septi (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study is generally aimed at analyzing the content of Indonesian language textbooks and providing valuable information for textbook developers and curriculum designers. Specifically, this research aims to describe: 1) the physical structure of the textbook, 2) the alignment of the textbook content with the learning outcomes in the merdeka curriculum, 3) the depth of the material presented in the textbook, 4) the accuracy of the material in the textbook, and 5) the overall quality of the Indonesian language textbook. The research employs a content analysis technique, with the primary data source being the Indonesian language textbook Cerdas Cergas Berbahasa dan Bersastra Indonesia for Grade X Senior High School. The findings of this study provide information regarding the feasibility of the textbook. Based on the analysis, the textbook demonstrates a highly comprehensive physical structure and excellent content feasibility. It meets the textbook content feasibility criteria, including alignment of the material with the learning outcomes, accuracy of the material, and the inclusion of supporting instructional materials.